Bahasa Inggris - Afifah, Hana; Susanto, Niken Hapsari Arimurti; Panunggul, Victor Bintang; Sitanini, Ayu; Putranto, Afif Hendri; Asrifah (Universitas Perwira Purbalingga, 2026)
Mocaf crackers are a processed product derived primarily from Mocaf flour. Mocaf flour is produced from cassava through a fermentation process involving microorganisms such as Rhizopus oryzae and yeast (Saccharomyces cerevisiae). The Women Farmers Group (Kelompok Wanita Tani, KWT) ERQU oversees the entire production chain of Mocaf crackers, ranging from raw material procurement to product marketing. This study aims to analyze the application of the marketing mix on Mocaf cracker products produced by KWT ERQU in Tumanggal Village, Pengadegan Subdistrict, Purbalingga Regency. The research was conducted in August 2024, employing a case study approach. Descriptive analysis was utilized to address the research objectives, based on the 8Ps marketing mix framework, which encompasses product, price, place, promotion, people, process, programs, and performance. The findings of the study reveal that the implementation of the 8P marketing mix in relation to Mocaf crackers produced by KWT ERQU requires further enhancement. In particular, improvements are needed in strengthening the product’s brand image, diversifying distribution channels, expanding promotional efforts—especially through digital media—establishing consistent marketing programs, conducting performance evaluations, and providing comprehensive training and guidance to KWT ERQU members. Such training should focus on hygienic production processes, product diversification, digital marketing strategies, packaging design quality enhancement, and customer service improvement. KEY WORDS: Mocaf Cracker, Marketing Strategy, Marketing Mix, MSME